Evaluating Letrozole and Tamoxifen Alone and in Sequence for Postmenopausal Women with Steroid Hormone Receptor-Positive Breast Cancer: the BIG 1-98 Randomized Clinical Trial at 8.1 years Median Follow-Up - Regan, Meredith M. (2011)
BACKGROUND: Postmenopausal women with hormone receptor-positive early breast cancer have persistent, long-term risk of breast cancer recurrence and death. Therefore, trials evaluating endocrine therapies for this patient population require extended follow-up. We present an update of efficacy outcomes in the Breast International Group (BIG) 1-98 study at 8.1 years median follow-up. METHODS: BIG 1-98 is a randomized, phase III, double-blind trial of 8010 postmenopausal women with hormone receptor-positive early breast cancer that compares five years of tamoxifen or letrozole monotherapy or sequential treatment with two years of one of these agents followed by three years of the other. The primary efficacy endpoint is disease-free survival (DFS: events comprise invasive breast cancer relapse, second primaries [contralateral breast and non-breast], or death without prior cancer event), and secondary endpoints are overall survival (OS), distant recurrence-free interval (DRFI) and breast cancer-free interval (BCFI). The monotherapy comparison includes patients randomized to tamoxifen × 5 years (n=2459) or letrozole × 5 years (n=2463). In 2005, after significant DFS benefit was reported for letrozole as compared with tamoxifen, a protocol amendment facilitated the crossover to letrozole of patients who were still receiving tamoxifen alone; Cox models and Kaplan-Meier estimates with inverse probability of censoring weighting (IPCW) are used to account for selective crossover to letrozole of 619 patients in the tamoxifen arm. The comparison of sequential treatments to letrozole monotherapy includes patients enrolled in the four-arm option of the trial and randomized to letrozole × 5 years (n=1546), letrozole × 2 years followed by tamoxifen × 3 years (n=1540), or tamoxifen × 2 years followed by letrozole × 3 years (n=1548). All patients have completed study treatment; follow up is continuing for those enrolled in the four-arm option. BIG 1-98 is registered at clinicaltrials.gov NCT00004205. FINDINGS: At a median follow-up of 8.7 years from randomization (range 0–12.4), letrozole monotherapy is significantly better than tamoxifen, whether using IPCW or intention-to-treat (ITT) analysis [IPCW: DFS HR 0.82 (95% CI 0.74–0.92), OS HR 0.79 (0.69–0.900, DRFI HR 0.79 (0.68–0.92), BCFI HR 0.80 (0.70–0.92); ITT: DFS HR 0.86 (0.78–0.96), OS HR 0.87 (0.77–0.999), DRFI HR 0.86 (0.74–0.998), BCFI HR 0.86 (0.76–0.98)]. At a median follow-up of 8.0 years from randomization (range 0–11.2), there were no statistically significant differences in any of the four endpoints for either sequence compared with letrozole monotherapy. Eight-year ITT estimates [each with SE ≤ 1.1%] for letrozole monotherapy, letrozole followed by tamoxifen, and tamoxifen followed by letrozole were 78.6%, 77.8%, 77.3% for DFS; 87.5%, 87.7%, 85.9% for OS; 89.9%, 88.7%, 88.1% for DRFI; and 86.1%, 85.3%, 84.3% for BCFI. INTERPRETATION: For postmenopausal women with endocrine-responsive early breast cancer, a reduction in breast cancer recurrence and mortality is obtained by letrozole monotherapy when compared to tamoxifen. Sequential treatments involving tamoxifen and letrozole do not improve outcome compared with letrozole monotherapy, but may represent useful strategies considering individual patient’s risk of recurrence and treatment tolerability: more thromboembolic events, vaginal bleeding, hot flushes and night sweats with tamoxifen, while more vaginal dryness, bone fractures, osteoporosis, arthralgia/myalgia, and higher grade cardiac events with letrozole. FUNDING: Novartis, United States National Cancer Institute, International Breast Cancer Study Group.